Greener through gender: What climate mainstreaming can learn from gender mainstreaming - Lam, Steven; Novović, G.; Skinner, K.; Hung Nguyen-Viet (Wiley, 2024)
Addressing the urgent global climate crisis demands a rapid and meaningful expansion of “climate mainstreaming,” which refers to the integration of climate objectives in all aspects of development programs and policies. However, progress remains slow and uneven due to bottlenecks in policy and institutional change. Considering the parallel struggle recorded over decades to mainstream gender across the same policy arenas, a key question emerges: what can climate mainstreaming learn from gender mainstreaming? To answer this question, we review 57 policy, strategy, and guidance documents of United Nations agencies, all of which integrate these themes into food security and broader development programming. Our analysis identifies gaps in climate mainstreaming efforts and derives lessons from gender mainstreaming to bridge these gaps. It underscores the importance of adapting programmatic mainstreaming strategies in response to evolving contexts, for example, by simultaneously considering both mainstreaming and targeted interventions. Additionally, it highlights the need to adopt organizational climate mainstreaming and establish mechanisms for accountability. Finally, it emphasizes the urgency of embracing a climate justice lens; in practice, this involves prioritizing populations at greater risk of climate change impacts and actively engaging diverse perspectives in decision-making, particularly communities facing multiple forms of discrimination.